2010
DOI: 10.1016/j.wem.2009.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Nonlinear Dynamics During Sudden Hypoxia at 8230 m Simulated Altitude

Abstract: The observed pattern of diminished linear HRV and increased nonlinear HRV is similar to that seen in subjects undergoing heavy exercise or in patients with ischemic heart disease at high risk for ventricular fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 28 publications
7
51
3
Order By: Relevance
“…The results of this study revealed that hypoxia reduces linear HRV, but it increases non-linear HRV. This pattern is similar to heavy exercise or high risk ischemic heart diseases (10). It has been shown that serum iron profile significantly increases with biphasic pattern in altitudes exposure in the hypobaric chamber (at 8,000 feet) for 8.5 hours (11).…”
Section: Introductionsupporting
confidence: 52%
“…The results of this study revealed that hypoxia reduces linear HRV, but it increases non-linear HRV. This pattern is similar to heavy exercise or high risk ischemic heart diseases (10). It has been shown that serum iron profile significantly increases with biphasic pattern in altitudes exposure in the hypobaric chamber (at 8,000 feet) for 8.5 hours (11).…”
Section: Introductionsupporting
confidence: 52%
“…Heart rate variability is also responsive to the changes in the ANS associated with external stimuli such as real or simulated altitude (21). For example, an initially sharp increase in sympathetic activity is observed upon arrival at altitude (7,28), which gradually declines through the acclimatization process (14,23). The reduction in HRV is largely due to a reduction in the parasympathetic drive at the sinus node during hypoxia, the mechanism behind which has been well described by Roche et al (20).…”
mentioning
confidence: 92%
“…However, the majority of the published data relate to short-term HRV recordings (1–5 min) obtained conducted in hypoxic chambers during ‘simulated’ rather than genuine terrestrial HA (Vigo et al, 2010; Prabhakaran and Tripathi, 2011; Mairer et al, 2013; Zhang et al, 2014). The hypoxic period examined has been generally brief (minutes to <8 h) with a tendency to assess at a single HA (Saito et al, 2005; Sutherland et al, 2017) leading to an under appreciation of the influence of acclimatization on HRV.…”
Section: Introductionmentioning
confidence: 99%